(untitled) (Hungarian Journal of Industry and Chemistry, 2010)
Through an example of an automotive component, the lecture introduces difficulties, arising during the turning operations of high silicon content aluminium castings. It evaluates the production, running currently with cutting fluid flood-type application; introduces the preliminary tests, carried out before change-over to the green manufacturing; furthermore, the circumstances of the tests, carried out with the method of DoE at High Speed Machining. The results of measurements, carried out with different tool materials and edge constructions, will be evaluated from the point of view of surface roughness minimisation. The results of topographic (3D) measurements of the machined surface will be compared with the results, gained with the electron-microscope; the disturbing phenomena, arising during the turning operation with diamond tool, will be analysed. Finally, the production circumstances will be determined in order to ensure the prescribed surface roughness - despite the increased productivity and the environmentally friendly cutting.